SISTEM AMONG, DALTON, DAN SHANTI NIKETAN Kajian Komparatif Historikal Sistem Pendidikan Indonesia, Amerika, dan India serta Implikasinya bagi Kemajuan Pendidikan di Indonesia Konteks Kekinian - Ahmad Tanaka (Jurnal Teknologi Pendidikan Madrasah, 2018)
This paper was library research in education system at three countries, it is Indonesia, United States America, and India were done by comparative analysis. It’s system is not descriptive education system on the three countries to present day. However, it was tried to trace education system which were applied by fouding fathers from three countries in his centuries. Nevertheless, in the fact its have correlation with contemporary education system. In addition to, to be lost diamond and to research. This paper were determined to deep analysis about benefit from three education systems, on macro education context or operational practice in learning. The three education system is indigenous education system were resulted from socialite education from its own country, its positive impact to national education system. Implied from education systems could be seek on many fact. Social fact, we concerned to character of nation, until we need back a character education were applied by Among system and Shanti Niketan, it would be relevant with our education system. Neither, like a education based on family, humanity education, learning by doing at Among system, friendship education, multi cultural education, enjoy learning moving class at Dalton system, natural class, boarding school at shanti niketan would be actual issue and to be a treasure which riched our educational system, present and future time.